2018
DOI: 10.1016/j.beproc.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high versus low levels of derivation for mutually and combinatorially entailed relations on persistent rule-following

Abstract: The effects of rules on human behaviour have long been identified as important in the psychological literature. The increasing importance of the dynamics of arbitrarily applicable relational responding (AARR), with regards to rules, has come to be of particular interest within Relational Frame Theory (RFT). One feature of AARR that previous research has suggested may differentially impact persistent rule-following is level of derivation. However, no published research to date has systematically explored this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 21 publications
1
51
1
Order By: Relevance
“…The results of Experiment 2 suggested that the derived rule had minimal impact on an MTS performance when the ‘meaning’ of the derived rule was reversed, but the original MTS contingencies were maintained. One important difference between the current study and the previous research reported by Harte et al (2017, 2018), and Harte, Barnes‐Holmes, Barnes‐Holmes, McEnteggart et al (2020) is that in these earlier studies, the MTS contingencies were reversed during exposure to the task but in the current study the contingencies remained unchanged (i.e., it was the derived rule that was reversed). Experiment 3 was a partial replication of Experiment 2, but the MTS procedure involved a reversal in the task contingencies.…”
Section: Methodscontrasting
confidence: 84%
See 4 more Smart Citations
“…The results of Experiment 2 suggested that the derived rule had minimal impact on an MTS performance when the ‘meaning’ of the derived rule was reversed, but the original MTS contingencies were maintained. One important difference between the current study and the previous research reported by Harte et al (2017, 2018), and Harte, Barnes‐Holmes, Barnes‐Holmes, McEnteggart et al (2020) is that in these earlier studies, the MTS contingencies were reversed during exposure to the task but in the current study the contingencies remained unchanged (i.e., it was the derived rule that was reversed). Experiment 3 was a partial replication of Experiment 2, but the MTS procedure involved a reversal in the task contingencies.…”
Section: Methodscontrasting
confidence: 84%
“…Following the rule was initially reinforced but the contingencies subsequently reversed and thus the rule now specified a direct contingency that no longer applied. This study and others that followed provided evidence that rules involving derived relations could override the impact of contact with direct contingencies (Bern et al, 2020; Harte et al, 2018; Harte, Barnes‐Holmes, Barnes‐Holmes, McEnteggart et al, 2020).…”
mentioning
confidence: 62%
See 3 more Smart Citations